METHOD OF PROTEIN EXTRACTION - JÓZWIAK, Michal; TRUSEK, Anna (2024)
The subject of the invention is a method of extracting protein from dried brewer's spent grain, which exists in the form of initial, unground granules (material with a diameter ranging from 3 to 6 cm) or ground granules (material with a diameter ranging from 0.3 to 2.9 cm) originating from beer production, i.e., spent grains. The protein extraction process occurs with the use of spent grains in an amount ranging from 20 to 350 grams per 1 litre of alkaline solution, for a period of 30 minutes to 48 hours under high-temperature conditions, i.e., at a temperature of at least 50°C. Subsequently, filtration or centrifugation is carried out to achieve a liquid mass fraction in the solid material below 30%. Purification of the protein solution, along with removal of the alkali, is performed using water on a membrane installation equipped with an ultrafiltration or dialysis membrane having pores ranging in size from 1 to 20 kDa.